The Influence of Perceived Value toward Customer Loyalty with Customer Satisfaction as the Mediating Variable: in the case of Boncafe - Billy Tanujaya (iBuss Management, 2018)
Restaurant industry, as one of the prominent sectors, is an industry with increasing competition and struggles. In the midst of intense competition, a restaurant’s retention strategy will decide its sustainability in the future.  Boncafe has been around for 40 years, but still need to understand the value perception of its customers and its influence on satisfaction and loyalty. Therefore, this research aims to find the influence of multidimensional perceived value toward customer loyalty with customer satisfaction as the mediating variable. This research is conducted by distributing questionnaires to 110 respondents who have dined in Boncafe, paid with their own money, and complaint to the employees about the food or service. The data was analyzed with path analysis and Sobel test. The findings conclude that loyalty can be attained by focusing on three major qualities of restaurant, namely food, service, and ambience. Furthermore, the findings also disprove the general perception that customer satisfaction leads to customer loyalty. Keywords:            Perceived Value, Functional Value, Emotional Value, Social Value,            Customer Satisfaction, Customer Loyalty